2020
DOI: 10.3390/diagnostics10090615
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Strongyloides Recombinant IgG Immunoreactive Antigen in Detecting IgG and IgG4 Subclass Antibodies for Diagnosis of Human Strongyloidiasis Using Rapid Immunochromatographic Tests

Abstract: Human strongyloidiasis is an important soil-transmitted helminthiasis that affects millions worldwide and can develop into fatal systemic strongyloidiasis in immunosuppressed patients. We have developed two new rapid and simple-to-use immunochromatographic test (ICT) kits for rapid serodiagnosis that support stool examination for clinical diagnosis. Strongyloides stercoralis recombinant IgG immunoreactive antigen (GenBank: AAB97359.1; rSsIR-based ICT kit) was used for detection of IgG and IgG4 antibodies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, studies comparing the IgG and the IgG4 formats of different assays for S. stercoralis diagnosis (including ELISAs, LIPS and another lateral flow cassette test), showed that the sensitivity of the IgG4 assay was dramatically lower than that of the IgG formats [ 11 , 21 , 22 ]. An ICT based on the recombinant antigen SsIR [ 23 ] showed 91.7% and 73.8% sensitivity with the IgG and IgG4 kits, respectively, while the specificity values were almost the same. Since the use of recombinant antigens is thought to produce more specific results than the use of crude antigens [ 11 ], an ICT that detects IgG would probably have the benefit of better sensitivity while retaining good specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies comparing the IgG and the IgG4 formats of different assays for S. stercoralis diagnosis (including ELISAs, LIPS and another lateral flow cassette test), showed that the sensitivity of the IgG4 assay was dramatically lower than that of the IgG formats [ 11 , 21 , 22 ]. An ICT based on the recombinant antigen SsIR [ 23 ] showed 91.7% and 73.8% sensitivity with the IgG and IgG4 kits, respectively, while the specificity values were almost the same. Since the use of recombinant antigens is thought to produce more specific results than the use of crude antigens [ 11 ], an ICT that detects IgG would probably have the benefit of better sensitivity while retaining good specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Our indirect IgG-ELISA diagnosis of strongyloidiasis, prepared from a modified molecular weight cut-off antigen, yielded a sensitivity and specificity of 96% and 94%, respectively, in immunocompetent hosts, and 42.9% and 96.3%, in immunocompromised hosts [ 27 , 28 ]. Recently, several sensitive and specific point-of-care serological tests for strongyloidiasis were developed and showed sensitivities and specificities of 91.3–93.3% and 83.8–100%, respectively [ 29 , 30 , 31 ]. The rapid point-of-care test also worked well in a field study, with 82% sensitivity and 96% specificity [ 32 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…9 Recently, there have been two reports on IgG4-based prototype lateral-flow dipstick rapid tests for strongyloidiasis. 10,11 One of them, SsRapid, lined with S. stercoralis recombinant NIE (rNIE) protein, showed good diagnostic value. 11,12 Hence, the present study assessed the concordance between a commercial IgG-ELISA and SsRapid.…”
mentioning
confidence: 99%